"To Make Some Extra Money": Smuggling and black marketeering by Czechoslovak transport workers (1970s and 1980s). Issue 3 (December 2021) - Krátká, Lenka
The paper focuses on various forms of illegal and semi-illegal activities, mainly smuggling and black marketeering as experienced by transport workers during the 1970s and 1980s in former Czechoslovakia. It is based primarily on several dozens of oral history interviews recorded with people from river, sea, air, and road transport. The interview analysis (together with archival resources) shows that while there were significant differences in the scope and types of these "transactions" in various transport fields, the risks and benefits were very similar. The second part reflects on "negotiations" between the uses of the opportunity to obtain money and goods abroad (sometimes in semi-illegal or illegal ways) and the fear of losing this chance, and eventually of losing the job, which was one of the most common punishments. This was a great threat, often more for the very love of the profession than for material benefits.